The age of hyperconflict and the globalization-terrorism nexus : a comparative study of Al Shabaab in Somalia and Boko Haram in Nigeria - Botma, Vasti (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.